Confucian heresy and religious imagination: a study of the renderings of Mozi by Protestantism missionaries in 19th century - Jiaxin Lin; Zihan Yu; Honghui Hu (Trans/Form/Ação)
Mozi first came to the English missionary Joseph Edkins’ attention in 1858 as a Confucian heretic. Subsequently, the Dutch missionary Johann Jakob Maria de Groot translated Mozi’s Funerary Doctrine, which has strong religious overtones. Protestantism missionaries were represented by Joseph and Groot, whose renderings of Mozi were replete with theological interpretations. Mozi was imagined as a religious canon, containing Christian doctrine, by the two missionaries who were keen to find commonalities between Mozi and Christianity. They also used Mozi’s status as a Confucian heretic to criticize Confucianism, the archenemy of Christianity. Through this religious imagination of Mozi, more missionaries and sinologists joined Mozi’s translation, and the journey of the canon’s transmission to the West started.